Analysis of Data Asset Management in Colleges and Universities - Ding, Hongfei; Liu, Yiqi; Xu, Mengqi; Lei, Qihong (Asia Pacific Economic and Management Review, 2025)
In the digital age, educational resources have become an important part of higher education institutions (HEI), and have improved teaching quality, scientific research output and administrative efficiency. Effective data asset management can greatly improve the decision-making process and resource allocation of higher education institutions. This study discusses the current situation of data asset management in higher education institutions, analyzes the challenges faced by data asset management, and puts forward strategies to improve data asset management. By analyzing some successful cases and drawing lessons from recent research experience, this paper aims to provide useful guidance for higher education institutions to make full use of their data assets and realize sustainable development in the digital age.